La peinture sur lave émaillée des façades des églises parisiennes du xixe siècle : une expérience de réintroduction de la polychromie - Josette Saint-Martin (Les Cahiers de l'École du Louvre)
The reintroduction of polychromy on the façades of nineteenth-century Parisian churches with paintings on enamelled lava took place, between 1827, the date on which Ferdinand-Henri-Joseph Mortelèque implement the first successful trials of painting on enamelled lava and, 1874, the date on which the tympana above the doors of the porch of the church of Saint-Joseph-des-Nations in the eleventh arrondissement were decorated by Paul Balze with paintings on enamelled lava. The study focuses on the six Paris churches with decoration painted on enamelled lava on the façade: Saint-Vincent-de-Paul, which to this day remains the best-known decoration in terms of its importance and history, La Sainte-Trinité, Saint-Augustin, Saint-Ambroise, Saint-Laurent and Saint-Joseph-des-Nations.Hypotheses have been put forwards as to the possible reasons, both technical and with regards to changing taste, which plunged the attempt to reintroduce polychromy on the façades of nineteenth-century Parisian churches in obscurity, until 1998, the year of the exhibition at the Musée de la Vie Romantique of the enamelled lavas of the church of Saint-Vincent-de-Paul.